(untitled) (Revista de Psicología, 2017)
This articule focuses on the problem of the functioning of adolescent’s families who reiterate the criminal behavior, emphasizing the analysis of the roles and parental coalitions. To achive this, the families and the young registered in the Juvenile Criminal Responsibility System, derived from the Criminal Offense of Minors of Mendoza, North Zone, Argentina, were approached. The methodological approach was a qualitative one; the Image Test of Family Relations (Usandivaras, 2004) was used as the main instrument of inquiry, which was taken from the families’home addresses obtained after the study of institutional records. The trial was administered to seventy-eigth people who constituted twenty-four families. As a result, a family functionig profile was obtained regarding patterns of integration, adaptability, cohesion and evolution of the group, as well as a description of the type of relationship between the parent and the juvenile offender of the criminal law. It is concluded that the tendency of families is oriented towars the regressive evolution, mothers do not exert the hierarchy proper of the maternal role, blurring boundaries by periphery or agglutination, and fathers show absence or periphery. Finally, the presence of gender issues is highlighted.